2013
DOI: 10.1007/s00128-013-0996-5
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Toxicity on Ludwigia octovalvis in Spiked Sand

Abstract: Wilting, especially of the leaves, was observed as an initial symptom of arsenate [As(V)] to Ludwigia octovalvis (Jacq.) P. H. Raven. The plants tolerated As(V) levels of 39 mg kg⁻¹ for as long as 35 days of exposure. After 91 days, the maximum concentration of As uptake in the plant occurred at As(V) concentration of 65 mg kg⁻¹ while As concentration in the stems, roots and leaves were 6139.9 ± 829.5, 1284.5 ± 242.9 and 1126.1 ± 117.2 mg kg⁻¹, respectively. In conclusion, As(V) could cause toxic effects in L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The wilting of leaves began at Day 3 in the NaCl concentration of 40,000 and 50,000 mg/L. According to Titah et al (2013a), the wilting, especially of the leaves, was observed as an initial symptom of phytotoxicity. However, the wilting leaves also occured at control and all salinity concentration at the end day of exposure (Day 7).…”
Section: Observation Of Physical On Survival Rhizophora Mucronatamentioning
confidence: 99%
“…The wilting of leaves began at Day 3 in the NaCl concentration of 40,000 and 50,000 mg/L. According to Titah et al (2013a), the wilting, especially of the leaves, was observed as an initial symptom of phytotoxicity. However, the wilting leaves also occured at control and all salinity concentration at the end day of exposure (Day 7).…”
Section: Observation Of Physical On Survival Rhizophora Mucronatamentioning
confidence: 99%
“…L. octovalvis is a plant species that can survive at a crude oil-contaminated site [16] and could uptake and accumulate arsenic in its tissues [17]. This study aimed to determine the level of arsenic (as arsenate) resistance of the identified rhizobacteria that were isolated from the roots of L. octovalvis grown in the greenhouse and contaminated land in Malacca, Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…L. octovalvis was chosen for this study since it was one of the plants that could survive contaminated site in Malaysia (Mushrifah 2011). According to Titah et al (2013) L. octovalvis could uptake and accumulate As in their tissue.…”
Section: Introductionmentioning
confidence: 99%